Regionalismen - Engel, Ulf (Dialektik des Globalen, 2018)
Regions have played a diverse part in the sovereignty strategies of specific national actors since the early 19th century. Since the end of the Cold War, they have become a preferred frame of reference in responding to current globalization processes - especially in the global South. This monograph introduces the reader to the often-fragmented interdisciplinary knowledge base on topics of regionality, including associated projects.